1974
DOI: 10.1136/oem.31.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of nasal mucociliary clearance in woodworkers in the furniture industry

Abstract: (1974). British Journal of Industrial Medicine, 31, 10-17. Impairment of nasal mucociliary clearance in woodworkers in the furniture industry. Measurements of mucociliary clearance from the anterior end of the middle turbinate were made using technetium-99m-labelled particles in nine woodworkers from the furniture industry and in 12 controls, none of whom had been occupationally exposed to wood dust. Clearance rates in the controls ranged from 1 9 to 18-5 mm min-' with a mean of 6-8. These values are in good a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 8 publications
1
26
0
Order By: Relevance
“…19,20,21 Obstructive respiratory effects, development of lung fibrosis, and impairment of the mucociliary clearance mechanism in the respiratory system have also been reported. 22,23 As a general rule, hard woods are more hazardous to human health than soft woods. One exception is western red cedar, a soft wood which has been identified as one of the most hazardous to human health.…”
Section: Wood Dust (As Total Dust)mentioning
confidence: 99%
“…19,20,21 Obstructive respiratory effects, development of lung fibrosis, and impairment of the mucociliary clearance mechanism in the respiratory system have also been reported. 22,23 As a general rule, hard woods are more hazardous to human health than soft woods. One exception is western red cedar, a soft wood which has been identified as one of the most hazardous to human health.…”
Section: Wood Dust (As Total Dust)mentioning
confidence: 99%
“…[33][34][35] Obstructive respiratory effects, development of lung fibrosis, and impairment of the mucocilliary clearance mechanism have also been reported. 34,36,37 In the majority of these studies, a particular type of wood has been identified as the causative agent of the particular health effect. Health effects unique to aspen wood dust has not been described.…”
Section: B Wood Dustmentioning
confidence: 99%
“…15,16,17 Obstructive respiratory effects, development of lung fibrosis, and impairment of the mucociliary clearance mechanism also have been reported. 18,19 The criteria for wood dust exposure are based on sampling for total dust with 37-mm closed faced cassettes. The OSHA PEL for wood dust (as total dust) is 15 mg/m 3 as an 8-hour TWA.…”
Section: Wood Dust (Measured As Total Dust)mentioning
confidence: 99%